A comparative analysis of fertility differentials in Ghana and Nigeria (2014)
Nigeria and Ghana are the most densely populated countries in the West African sub-region with fertility levels above world average. Our study compared the two countries’ fertility levels and their determinants as well as the differentials in the effect of these factors across the two countries. We carried out a retrospective analysis of data from the Nigeria and Ghana Demographic Health Surveys, 2008. The sample of 33,385 and 4,916 women aged 15-49 years obtained in Nigeria and Ghana respectively was stratified into low, medium and high fertility using reported children ever born. Data was summarized using appropriate descriptive statistics. Factors influencing fertility were identified using ordinal logistic regression at 5% significance level. While unemployment significantly lowers fertility in Nigeria, it wasn’t significant in Ghana. In both countries, education, age at first marriage, marital status, urban-rural residence, wealth index and use of oral contraception were the main factors influencing high fertility levels.